A critical analysis of halal marketing in Malaysia's multi-level marketing (MLM) industry - Shamsiah Yaakob (International Institute for Halal Research and Training, International Islamic University Malaysia, 2020)
The concept of halal is based on the Hadith narrated by Imam Muslim “Allah is Pure and Takes Nothing except that which is Pure”. This is not limited to the consumable things but it relates to all activities of one's life. Indeed, the life is given to each human for nothing but for worshipping Allah alone. Worship in Islam takes many different ways, which one of them is through the business and trading. Business itself is broken down into many different kinds, one of those which has become nowadays trend is Multi Level Marketing (MLM). MLM business is a business model that involves selling and recruitment of new distributors inside the company. Multi Level Marketing is seen to be good as it helps many people to achieve their dreams, but in contrary, it is observed as a medium of cheating that promises wealth to a few by oppressing the poor and uneducated ones. With its players reaching to 2 million in Malaysia since its establishment in early 1990s, MLM's presence in the business industry should not be taken lightly.This factors include the system itself manufacturing, the distribution channels, the after-sales service, and the long-run vision of the company. By doing this, it is aimed that the doubtful or even the unlawful (haram) practice of MLM can be eliminated and abstained by the Muslim players and better MLM companies can be established, using proper S.O.P and guidelines. The objectives of the research are gained through the library method and interviews.